Bayesian estimates of male and female African lion mortality for future use in population management. Issue 2 (April 2016) - Barthold, Julia A.; Loveridge, Andrew J.; Macdonald, David W.; Packer, Craig; Colchero, Fernando
Summary: The global population size of African lions is plummeting, and many small fragmented populations face local extinction. Extinction risks are amplified through the common practice of trophy hunting for males, which makes setting sustainable hunting quotas a vital task. Various demographic models evaluate consequences of hunting on lion population growth. However, none of the models use unbiased estimates of male age‐specific mortality because such estimates do not exist. Until now, estimating mortality from resighting records of marked males has been impossible due to the uncertain fates of disappeared individuals: dispersal or death. We develop a new method and infer mortality for male and female lions from two populations that are typical with respect to their experienced levels of human impact. We found that mortality of both sexes differed between the populations and that males had higher mortality across all ages in both populations. We discuss the role that different drivers of lion mortality may play in explaining these differences and whether their effects need to be included in lion demographic models. Synthesis and applications . Our mortality estimates can be used to improve lion population management and, in addition, the mortality model itself has potential applications in demographically informed approaches to the conservation of species with sex‐biased dispersal. Abstract : Our mortality estimates can be used to improve lion population management and, in addition, the mortality model itself has potential applications in demographically informed approaches to the conservation of species with sex‐biased dispersal.